Inspecting the Influence of Transformational Leadership on Entrepreneurial Performance in Regional Development Project Companies - Nassif J. Alkhattabi; Joumana A. Younis; Hayder A. H.Al-Juboori (Decision Making: Applications in Management and Engineering, 2025)
This study examines the impact of transformational leadership on entrepreneurial performance, focusing on five fundamental leadership dimensions. A quantitative research methodology was adopted, employing a structured questionnaire to operationalise transformational leadership in alignment with the study’s objectives. A deductive approach was utilised to formulate hypotheses. The research sample comprised 380 employees from Regional Development Project Companies in Karbala, selected through a random sampling technique. The findings indicate that idealised influence exerts the strongest effect on entrepreneurial performance. Additionally, both inspirational motivation and individualised consideration produced significant estimates, highlighting the importance of addressing employees’ unique needs. Intellectual stimulation also exhibited a positive association with entrepreneurial performance, underscoring the necessity of fostering innovative thinking within the workforce. Moreover, empowerment emerged as a critical factor in enhancing entrepreneurial outcomes. Statistical analyses supported these conclusions, with goodness-of-fit indices confirming a well-calibrated model (GFI = 0.908, AGFI = 0.907, IFI = 0.920, χ² = 2.1, RMSEA = 0.071, P = 0.00). These metrics validate the model’s statistical soundness. As a result, Regional Development Project Companies should prioritise these transformational leadership dimensions to improve entrepreneurial performance. By equipping both current and emerging leaders with transformational leadership capabilities, organisations can enhance overall performance, drive innovation, and improve adaptability to changing environmental conditions.